Organizational Commitment, Professional Work Behavior, and Teacher Performance in Private Islamic Senior Secondary Schools: A Qualitative Multi-Site Study in Indonesia - Tupan (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
Teacher performance in private Islamic senior secondary schools is shaped not only by formal competence but also by teachers' attachment to the institutional mission. This qualitative multi-site study examines how organizational commitment is enacted through daily work behavior and translated into teacher performance in three private Islamic senior secondary schools in Bandar Lampung, Indonesia. Data were generated through semi-structured interviews with teachers, school principals, and educational staff; non-participant observations of instructional and organizational routines; and institutional documents. Iterative thematic analysis identified three connected forms of commitment: affective commitment, normative commitment, and continuance commitment. Affective commitment fostered initiative, collaboration, and sustained instructional preparation, whereas normative commitment drew strength from Islamic ethical concepts of amanah (trustworthiness), ikhlas (sincerity), and service. Continuance commitment promoted retention but, on its own, was less associated with proactive or innovative practice. Across sites, participatory leadership, professional recognition, supportive supervision, and collaborative learning strengthened affective and normative commitment. The study contributes a value-based organizational commitment model that locates teacher performance within Islamic educational leadership, culture, and professional learning.